Nanoparticles as Potential Antivirals in Agriculture - Vargas-Hernandez, Marcela; Macias-Bobadilla, Israel; Guevara-Gonzalez, Ramon Gerardo; Rico-Garcia, Enrique; Ocampo-Velazquez, Rosalia Virginia; Avila-Juarez, Luciano; Torres-Pacheco, Irineo (Agriculture (Basel), 2020)
Viruses are estimated to be responsible for approximately 50% of the emerging plant diseases, which are difficult to control, and in some cases, there is no cure. It is essential to develop therapy practices to strengthen the management of these diseases caused by viruses in economically important crops. Metal nanoparticles (MeNPs) possess diverse physicochemical properties that allow for them to have a wide range of applications in industry, including nanomedicine and nano-agriculture. Currently, there are reports of favorable effects of the use of nanoparticles, such as antibacterial, antifungal, and antiviral effects, in animals and plants. The potential antiviral property of MeNPs makes them a powerful option for controlling these histological agents. It is crucial to determine the dosage of NPs, the application intervals, their effect as a biostimulant, and the clarification of the mechanisms of action, which are not fully understood. Therefore, this review focuses on discussing the ability of metal nanoparticles and metal oxides to control viruses that affect agriculture through an exhaustive analysis of the characteristics of the particles and their interaction processes for a possibly beneficial effect on plants.